X-ray eclipse mapping constrains the binary inclination and mass ratio of Swift J1858.6−0814. Issue 2 (13th May 2022) - Knight, Amy H; Ingram, Adam; Middleton, Matthew
ABSTRACT: X-ray eclipse mapping is a promising modelling technique, capable of constraining the mass and/or radius of neutron stars (NSs) or black holes (BHs) in eclipsing binaries and probing any structure surrounding the companion star. In eclipsing systems, the binary inclination, i, and mass ratio, q relate via the duration of totality, t e . The degeneracy between i and q can then be broken through detailed modelling of the eclipse profile. Here, we model the eclipses of the NS low-mass X-ray binary Swift J1858.6−0814 utilizing archival NICER observations taken while the source was in outburst. Analogous to EXO 0748−676, we find evidence for irradiation driven ablation of the companion's surface by requiring a layer of stellar material to surround the companion star in our modelling. This material layer extends ∼7000–14 000 km from the companion's surface and is likely the cause of the extended, energy-dependent and asymmetric ingress and egress that we observe. Our fits return an inclination of i ∼ 81 ○ and a mass ratio q ∼ 0.14. Using Kepler's law to relate the mass and radius of the companion star via the orbital period (∼21.3 h), we subsequently determine the companion to have a low mass in the range 0.183 M⊙ ≤ M cs ≤ 0.372 M⊙ and a large radius in the range 1.02 R⊙ ≤ R cs ≤ 1.29 R⊙ . Our results, combined with future radial velocity amplitudes measured from stellar absorption/emission lines, can place precise constraints on the component masses in this system.